Analisis Aspek Pengelolaan Sampah di TPS 3R Sauyunan Hegarmanah Kecamatan Jatinangor Menggunakan Metode Regresi Logistik - I Made Wahyu Widyarsana; Khairunisa; Ninne Sevtiana Dewi; Qurratu ‘Ainy Meilita; Rizal Husni Nurulloh (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Jainangor District is a district in Sumedang Regency and has been designated as a higher education strategic area. Due to rapid population growth, household waste production has reached 37,096 tonnes per day. Considering the Local Regulation of Sumedang Regency No. 2/2014 on the Management of Household Waste and Similar Household Waste and the Legal Regulation of the President of Indonesia No. 97/2017 on the National Policy and Strategy for the Management of Household Waste and Similar Household Waste, sustainability is a crucial approach to reduce waste production. However, due to the suboptimal operation of TPS 3R Sauyunan Hegarmanah, a sustainability study of TPS 3R is conducted to determine the factors affecting the sustainability of TPS 3R, considering both technical and non-technical aspects, and to identify models of sustainability aspects of TPS 3R using logistic regression method. The logistic regression analysis, carried out using SPSS software with a 95% confidence level, shows that institutional factors are the most significant in determining the continuity of TPS 3R (p-value = 0.435). Furthermore, assessment of financial sustainability shows that the average community's ability to pay (ATP) exceeds their willingness to pay (WTP), indicating a lack of perceived urgency among respondents regarding the level of services provided by the TPS 3Rs